2002
DOI: 10.1152/ajprenal.00218.2001
|View full text |Cite
|
Sign up to set email alerts
|

Production of superoxide through NADH oxidase in thick ascending limb of Henle's loop in rat kidney

Abstract: We recently reported that NADH oxidase is one of the major enzymes responsible for superoxide (O(2)(-)*) production in the rat kidney. However, the functional significance of NADH oxidase-mediated O. production and the mechanisms regulating this enzyme activity are poorly understood. Using fluorescence microscopic imaging analysis, the present study demonstrated that thick ascending limbs of Henle's loop (TALHs) exhibited red fluorescence when incubated with dihydroethidium (DHE), suggesting that O(2)(-)* is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
121
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 46 publications
9
121
1
Order By: Relevance
“…NAD(P)H oxidase, as well as other metabolic oxidases such as xanthine oxidase and mitochondrial respiratory chain enzymes (I-IV), are functional in the kidney (278). However, we and others have identified NAD(P)H oxidase-induced ROS production as a primary initiator of oxidative stress within the kidney (183,353,355,356 onists that bind to D1-like receptors, and to H ϩ fluxes (28,89,146,184,259,353,377,384) (Figs. 6 through 9).…”
Section: Nistala Et Al 2060mentioning
confidence: 89%
“…NAD(P)H oxidase, as well as other metabolic oxidases such as xanthine oxidase and mitochondrial respiratory chain enzymes (I-IV), are functional in the kidney (278). However, we and others have identified NAD(P)H oxidase-induced ROS production as a primary initiator of oxidative stress within the kidney (183,353,355,356 onists that bind to D1-like receptors, and to H ϩ fluxes (28,89,146,184,259,353,377,384) (Figs. 6 through 9).…”
Section: Nistala Et Al 2060mentioning
confidence: 89%
“…We have demonstrated previously that O 2 ⅐Ϫ production in the kidney of normotensive SD rats is predominately produced by NAD(P)H oxidase localized in thick ascending limb segments of the cortex and the outer medulla. 29,30 Immunohistochemistry of the NADH oxidase subunit gp91 phox has shown that the highest level of staining is in the outer medulla, with less staining in the cortex and no signal in the papilla. 30 In contrast, the cortex appears to have a higher antioxidant capacity than the medulla, because SOD, catalase, and GPx activities were highest in the cortex of kidneys from Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…NAD(P)H oxidase has been assigned a major role in ROS generation in vascular and cardiac tissue with contributions from other sources such as xanthine oxidase and mitochondrial respiration (8). In the kidney, NAD(P)H oxidase mediates production of O 2 ·Ϫ in mesangial cells (27), thick ascending limb cells (16), and rat renal medullary homogenates (15). Thus, this oxidase may play a critical role in producing ROS in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The p47 phox is a critical regulatory subunit required for assembly and activation of NADPH oxidase (2). Both gp91 phox and p47 phox are highly expressed in the thick ascending limb and distal nephron (14,16), where ROS can enhance tubular Na ϩ reabsorption (16). All components of phagocyte NAD(P)H oxidase are expressed in the macula densa, where they may impair the effects of NO on tubuloglomerular feedback responses (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation